Assessing Pre-service Teachers Prior to Certification: Perspectives on the Performance Assessment for California Teachers (PACT) - Okhremtchouk, Irina; Newell, Patrick; Rosa, Rebecca (Education Policy Analysis Archives, 2013)
This study focuses on pre-service teachers’ perspectives regarding how the process of completing the Performance Assessment for California Teachers (PACT) affected them academically, professionally, and personally. Two cohorts participated in this year-two study. Pre-service teachers’ perspectives were acquired using a survey instrument comprised of open-ended questions. In addition, pre-service teachers’ self-confidence levels pertaining to assessment task components of PACT (i.e., planning, instruction, assessment, reflection, and academic language) were measured prior to the execution of PACT portfolio assessment and these levels were compared to the actual scores on PACT. This study concludes with implications for teacher educators and teacher education programs implementing pre-service teacher assessments; these implications include policy level suggestions as well as a discussion of intended and unintended consequences of the PACT assessment on the pre-service teachers.